Trading Our Way out of War: Perpetual Peace without Politics - Vieira,Patrícia (2018)
Proponents of perpetual peace have often identified politics as a problem standing in the way of peaceful relations between humans. They believed that, while politics exacerbates the differences separating nations, commerce brings human beings together. In this article, I trace the development of arguments against politics and for commerce from the late fifteenth to the early nineteenth century. I argue that thinkers espoused an idealized view of commerce as an activity that fostered the development of a peaceful international community, while gradually eliminating economic inequalities. I also highlight how these arguments still resonate with today's debates on globalization.